Cell type-dependent expression of tubulins in Physarum. - Burland, T; Gull, K; Schedl, T; Boston, R; Dove, W (1983)
Three alpha-tubulins and two beta-tubulins have been resolved by two-dimensional gel electrophoresis of whole cell lysates of Physarum myxamoebae or plasmodia. Criteria used to identify the tubulins included migration on two-dimensional gels with myxamoebal tubulins purified by self-assembly into microtubules in vitro, peptide mapping with Staphylococcus V8 protease and with chymotrypsin, immunoprecipitation with a monoclonal antibody specific for beta-tubulin, and, finally, hybrid selection of specific mRNA by cloned tubulin DNA sequences, followed by translation in vitro. Differential expression of the Physarum tubulins was observed. The alpha 1- and beta 1-tubulins were detected in both myxamoebae and plasmodia; alpha 2 and beta 2 were detected only in plasmodia, alpha 3 was detected only in the myxamoebal phase, and may be specific to the flagellate. Observation of more tubulin species in plasmodia than in myxamoebae was remarkable; the only microtubules detected in plasmodia are those of the mitotoic spindle, whereas myxamoebae display cytoplasmic, centriolar, flagellar, and mitotic-spindle microtubules. In vitro translation of myxamoebal and plasmodial RNAs indicated that there are distinct mRNAs, and therefore probably separate genes, for the alpha 1-, alpha 2-, beta 1-, and beta 2-tubulins. Thus, the different patterns of tubulin expression in myxamoebae and plasmodia reflect differential expression of tubulin genes.